Cheese Market in Moscow and the Moscow Region: A Regional Analysis - Sergei N. Chebotarev; Zhanna N. Dibrova; Natalya M. Suray (Техника и технология пищевых производств)
Introduction. Cheese production is a promising niche with high profitability and excellent growth prospects. The city of Moscow and the Moscow region are the largest producers of cheeses and cheese products in Russia. Cheese production is developing there as part of the import substitution policy. The article describes some promising development directions of the local cheese industry. Study objects and methods. The paper analyzes and generalizes recent research publications, as well as regulatory and legislative documents, from legislative, statistical, and diagnostic positions. Results and discussion. The Moscow Region ranks second in the Central Federal District in terms of gross milk production; its indicator was 700 000 tons by the end of 2020. In 2016–2020, the list of leading cheese-producing areas included the regions of Altai, Moscow, Bryansk, Belgorod, and Voronezh. In Moscow and the Moscow region, the largest share in the structure of cheese production belongs to semi-hard cheeses followed by whizzed and soft cheese, with the annual consumption of cheese of 7 kg. Conclusion. The article features the current state of cheese market in the city of Moscow and the Moscow region, its development prospects, structure, production dynamics, consumption rate, etc. The paper also contains a forecast of the regional cheese production based on new production technologies and assortment policy.